Glycopyrronium Bromide is superior to Trihexyphenidyl for reducing drooling in children with cerebral palsy—An unregistered randomized controlled trial - Happy, Romana Akter; Debnath, Bithi; Saha, Narayan Chandra; Hoque, Seikh Azimul; Begum, Mosammat Shameem Ara; Quiraishi, Soabraj Al; Islam, Tithi; Sultana, Taslima (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Background: Cerebral palsy is frequently associated with drooling or anterior sialorrhoea. This study was aimed to compare the efficacy of Glycopyrronium bromide and Trihexyphenidyl to reduce drooling in children with cerebral palsy (CP). Materials and Methods: A single-centered, unregistered, randomized controlled trial was conducted from January to December 2022 on 100 children (aged 3–14 years) diagnosed with CP. The patients receiving conservative therapy without any medical or surgical intervention were included in the study. The study subjects were divided into two groups: 50 received oral glycopyrronium bromide, and 50 received oral trihexyphenidyl. Glycopyrronium bromide was administered starting at 0.02 mg/kg three times daily, titrated up to 0.1 mg/kg. Trihexyphenidyl was administered starting at 1 mg daily, increasing to a maximum of 2 mg three times a day. Follow-ups were conducted at 1, 3, and 6 months to assess drooling severity and frequency using the Thomas Stonell and Greenberg drooling rating scale. Results: Glycopyrronium bromide was found to be more effective at 3 months in terms of only frequency (p= 0.02) but in terms of severity, which was statistically not significant. And at 6 months in terms of both frequency (p=0.00.9) and severity (p=0.001) of drooling was significantly improved with glycopyrronium bromide in comparison to trihexyphenidyl. Conclusion: Oral glycopyrronium bromide was found to be significantly more effective than trihexyphenidyl at 3 months and 6 months to reduce drooling in children with cerebral palsy and side effects of both drugs are almost similar. J Bangladesh Coll Phys Surg 2026; 44: 11-16